Scottish tragic ballads. - Pinkerton, John, 1758-1826, editor. (Tufts University. Tisch Library., 2016)
1 online resource (xxxvii, [1], 130 pages); Title vignette.; Edited by John Pinkerton, who in his "Ancient Scotish poems, never before in print ... 1786" (v.1, p.cxxviii-cxxxi) admitted the authorship of the second part of Hardyknute and several of the other poems.; Subsequently published in 2 v., with additions, under title: Select Scotish ballads, 1783.; Signatures: a-b⁸ c⁴ ( -c4) B-I⁸ K1.; Engraved title ill.; "Dissertations on the oral tradition of poetry, and on the tragic ballad": p.[vii]-xxxvii.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.